Isotopic evidence for dietary diversity at the mediaeval Islamic necropolis of Can Fonoll (10th to 13th centuries CE), Ibiza, Spain - Pickard, Catriona; Girdwood, Laura-Kate; Kranioti, Elena F.; Márquez-Grant, Nicholas; Richards, Michael P.; Fuller, Benjamin T. (Elsevier, 2018)
The diet of the population interred at the Islamic necropolis of Can Fonoll, Ibiza, Spain, which was in use between the 10th and 13th centuries AD, is reconstructed from the carbon (δ13C) and nitrogen (δ15N) stable isotope ratios of bone collagen from 112 individuals. The mean ± sd (1σ) δ13C (− 19.0 ± 1.3‰) and δ15N (10.3 ± 0.8‰) values of the Can Fonoll population indicate a diet based largely on terrestrial C3 resources. However, the wide range of both δ13C (− 20.6‰ to − 8.6‰) and δ15N (7.0‰ to 12.1‰) values attested at Can Fonoll indicate significant variation in individual diet. The elevated δ13C values of a small proportion of the individuals buried at Can Fonoll are consistent with the consumption of a large proportion of, or dependence on, C4 resources, such as millet. Comparison of the δ13C and δ15N values of the Can Fonoll population with those of other mediaeval populations from the Balearic Islands and mainland Spain highlights a wide range of stable isotope values, which reflects not only significant differences in diet but also points to widespread mobility within the Mediterranean Basin.
Keywords: C4; Ibiza; Islamic; Millet; Stable isotopes